2014
DOI: 10.1186/1471-2164-15-776
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the genetic basis of microcystin tolerance

Abstract: BackgroundCyanobacteria constitute a serious threat to freshwater ecosystems by producing toxic secondary metabolites, e.g. microcystins. These microcystins have been shown to harm livestock, pets and humans and to affect ecosystem service and functioning. Cyanobacterial blooms are increasing worldwide in intensity and frequency due to eutrophication and global warming. However, Daphnia, the main grazer of planktonic algae and cyanobacteria, has been shown to be able to suppress bloom-forming cyanobacteria and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 48 publications
(67 reference statements)
3
44
0
Order By: Relevance
“…Through the application of a transcriptome‐wide top‐down strategy, we had access to recognize the genes and complicated pathways involved in cyanobacteria tolerance in Daphnia populations. As expected, not only did we discover evidence compatible with previous results (Asselman et al , ; Schwarzenberger et al ), but we also identify novel candidate pathways that accounted extensively for the tolerance of Daphnia to cyanobacteria. There was a total of 1864 DGEs that highlighted the pathways of glutathione metabolism, protein processing in endoplasmic reticulum, amino sugar/nucleotide sugar metabolism, and arachidonic acid metabolism (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Through the application of a transcriptome‐wide top‐down strategy, we had access to recognize the genes and complicated pathways involved in cyanobacteria tolerance in Daphnia populations. As expected, not only did we discover evidence compatible with previous results (Asselman et al , ; Schwarzenberger et al ), but we also identify novel candidate pathways that accounted extensively for the tolerance of Daphnia to cyanobacteria. There was a total of 1864 DGEs that highlighted the pathways of glutathione metabolism, protein processing in endoplasmic reticulum, amino sugar/nucleotide sugar metabolism, and arachidonic acid metabolism (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Three biological replicates were analyzed for each food treatment, which was administered to each clone in a steady photoperiod of 14 : 10 h (light/dark) cycle and at 25°C. The body growth rates (BGRs) of the D. similoides clones were determined from the body dry weight of a subsample of the animals at the beginning and end of the experiment (Day 7), calculated based on the study (Schwarzenberger et al ). Number of molting was examined by counting shed carapaces.…”
Section: Methodsmentioning
confidence: 99%
“…Given that excreting microcystins process is energy-dependent (Campos and Vasconcelos, 2010;Bieczynski et al, 2014), it is reasonable that elevated Dm-AK expression and ATP content may promote microcystins excretion. Hence, our results together with results of Schwarzenberger et al (2009Schwarzenberger et al ( , 2014 could partly explain why subsequent offspring had higher fitness when the previous generation had been exposed to toxic Microcystis. Further studies on the gene-regulated pathways involving maternal effects in Daphnia are necessary, in light of the publication of the Daphnia genome (Colbourne et al, 2011) which brings Daphnia research into a new era where we face the challenging task of connecting genome structure, function and expression with variation in ecologically important traits.…”
Section: Discussionsupporting
confidence: 51%
“…A candidate gene study of D. magna identified that three genes involved in glycolysis and the tricarboxylic acid cycle were up-regulated 8-10 folds in individuals exposed to toxic Microcystis relative to those exposed to non-toxic strains (Schwarzenberger et al, 2009). Moreover, Schwarzenberger et al (2014) recently reported that the increases of permeases gene expression were detected in the tolerant Daphnia clone, leading to higher production of transporter protein, which subsequently results in a stronger excretion of microcystins from the cells. Given that excreting microcystins process is energy-dependent (Campos and Vasconcelos, 2010;Bieczynski et al, 2014), it is reasonable that elevated Dm-AK expression and ATP content may promote microcystins excretion.…”
Section: Discussionmentioning
confidence: 95%
“…However, only a few target genes in combination with their functional role in local adaptation have been identified. One study connecting target genes with the origin of Daphnia clones was from Schwarzenberger et al (). Here, four D. magna genotypes from ponds with or without microcystin‐producing cyanobacteria differed in the expression of transporter genes which was associated with differences in tolerance to microcystin.…”
Section: Introductionmentioning
confidence: 99%